2022
DOI: 10.3390/su142215337
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Textiles from Hemp Biomass: Opportunities and Challenges

Abstract: Worldwide demand for man-made cellulosic fibres (MMCF) are increasing as availability of cotton fibre declines due to climate change. Feedstock for MMCF include virgin wood, agricultural residues (e.g., straw), and pre- and post-consumer cellulosic materials high in alpha-cellulose content. Lyocell MMCF (L-MMCF) offer large advantages over other MMCF processes in terms of both environmental and social impacts: the solvent for cellulosic dissolution, n-methyl-morpholine-n-oxide, can be recycled, and the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Hemp fiber was chosen as the research object because it is a typical plant fiber found from the stem of the hemp plant and has carbon-storage capacity, higher biomass output, and various end-use products [18]. Furthermore, hemp is considered as a preferential cellulosic raw material as cultivation results in CO 2 storage, and it requires less water, fertilizers, pesticides, and herbicides than other plant-derived fibers [19]. A case study was implemented to evaluate the carbon storage and temporary carbon storage effects of three 100% hemp fiber products, and also to provide a reference for future carbon footprint systematic assessment of plant fiber products.…”
Section: Introductionmentioning
confidence: 99%
“…Hemp fiber was chosen as the research object because it is a typical plant fiber found from the stem of the hemp plant and has carbon-storage capacity, higher biomass output, and various end-use products [18]. Furthermore, hemp is considered as a preferential cellulosic raw material as cultivation results in CO 2 storage, and it requires less water, fertilizers, pesticides, and herbicides than other plant-derived fibers [19]. A case study was implemented to evaluate the carbon storage and temporary carbon storage effects of three 100% hemp fiber products, and also to provide a reference for future carbon footprint systematic assessment of plant fiber products.…”
Section: Introductionmentioning
confidence: 99%
“…Table 2. Cellulose content in some plants [14][15][16][17]. Leveraging this resource as a renewable source of cellulose fibers presents a more sustainable strategy for mitigating substantial volumes of agro-residue.…”
Section: Fibermentioning
confidence: 99%
“…The L-MMCF is known to be environmentally friendly, in comparison with the rayon viscose process. With sustainability and environmental initiatives increasing worldwide, as well as the widening of the Cellulose Gap, L-MMCF are a logical choice for cellulosic manufacturing applications [5][6][7][8][9][10][11]. Table 1 outlines the advantages and disadvantages of the L-MMCF process in comparison to the viscose process.…”
Section: Introductionmentioning
confidence: 99%
“…Canopy defines endangered and ancient forests as "intact forest landscape mosaics, naturally rate forest types, forest types that have been made rare due to human activity, and/or other forests that are ecologically critical for the protection of biological diversity" [14]. Current feedstock for L-MMCF include cotton linters, wood (e.g., eucalyptus, beech), and grasses (i.e., bamboo) [1,11,[15][16][17][18][19][20][21][22]; smaller quantities of L-MMCF have been evaluated from residual agricultural biomass (e.g., hemp, bagasse, corn cobs, citrus biproducts, flax noils, kudzu vines, kenaf) [7,12,19,[22][23][24][25][26][27][28][29][30][31][32], as well as recycled cellulosic textiles commercialised with the Refriba™ technology towards Tencel™ manufacturing [12,33,34]. Agricultural residues and recycled cellulosic textiles as a feedstock for L-MMCF offer new perspectives for sustainable feedstock sourcing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation